The Frobenius number associated with the number of representations for sequences of repunits - Komatsu, Takao (Comptes Rendus. Mathématique)
The generalized Frobenius number is the largest integer represented in at most $p$ ways by a linear combination of nonnegative integers of given positive integers $a_1,a_2,\,… ,\,a_k$. When $p=0$, it reduces to the classical Frobenius number. In this paper, we give the generalized Frobenius number when $a_j=(b^{n+j-1}-1)/ (b-1)$ ($b\ge 2$) as a generalization of the result of $p=0$ in [16].